Acute Pancreatitis as a Possible Unusual Manifestation of COVID-19 in Children - Niloufar Bineshfar; Alireza Mirahmadi; Fereshteh Karbasian; Elham Pourbakhtyaran; Abdollah Karimi; Mehdi Sarafi (Case Reports in Pediatrics)
Coronavirus disease-2019 (COVID-19) which is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has spread throughout the world causing problems for millions of people. Symptoms of COVID-19 in pediatric patients include both respiratory and gastrointestinal symptoms. The most common symptoms are fever, cough, and fatigue. In this report, we describe a case of a previously well 14-year-old boy, who presented to our emergency department with a complaint of abdominal pain, nausea, and vomiting without fever or respiratory symptoms. He was diagnosed with acute pancreatitis based on an abnormal amylase level and abdomen computed tomography (CT) and later found to be infected by SARS-CoV-2, by a positive reverse transcriptase-polymerase chain reaction (RT-PCR) test.